2014
DOI: 10.1002/cncr.28681
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a characteristic copy number alteration profile by high‐resolution single nucleotide polymorphism arrays associated with metastatic sporadic colorectal cancer

Abstract: BACKGROUND: Metastatic dissemination is the most frequent cause of death in patients with sporadic colorectal cancer (sCRC). It is believed that the metastatic process is related at least in part to a specific background of genetic alterations accumulated in cells from primary tumors, and the ability to detect such alterations is critical for the identification of patients with sCRC who are at risk of developing metastases. METHODS: The authors used high-resolution, 500-K single nucleotide polymorphism arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…29 Yet another study identified more deletions of chr1p, 17p and 18q and gains of chr7 and 13q in metastatic CRC. 30 These associations deserve further validation in larger populations of more regions and species.…”
Section: Cnas In Crcmentioning
confidence: 95%
See 3 more Smart Citations
“…29 Yet another study identified more deletions of chr1p, 17p and 18q and gains of chr7 and 13q in metastatic CRC. 30 These associations deserve further validation in larger populations of more regions and species.…”
Section: Cnas In Crcmentioning
confidence: 95%
“…The CYP3A5 and CYP3A7 genes have been frequently found upregulated in primary CRCs. 30,106 Moreover, the PODXL gene (7q32) is associated with CRC metastasis 107 and poor survival 108 because of its function in cell adhesion and invasion. The RAPGEF5 (Rap guaninenucleotide exchange factor 5) gene located at 7p15.3 catalyzes the activation of RAS by promoting acquisition of guanosine triphosphate (GTP) to maintain the active GTP-bound state, and is the key link between cell surface receptors and RAS activation.…”
Section: Chr7mentioning
confidence: 99%
See 2 more Smart Citations
“…Copy number variations (CNVs) have been used to determine prognosis and subsequent treatment profile for a number of cancers, e.g., MYCN amplification for neuroblastoma (6). Comparisons between CNV of genes in primary CRC tumors and their matched metastatic disease sites are well documented, but less is known about how CNV of genes in CRC primary tumors differs between those associated with localized disease compared with those associated with distant metastatic disease (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%